2020
DOI: 10.21037/atm.2020.04.39
|View full text |Cite
|
Sign up to set email alerts
|

A deep learning, image based approach for automated diagnosis for inflammatory skin diseases

Abstract: Background: As the booming of deep learning era, especially the advances in convolutional neural networks (CNNs), CNNs have been applied in medicine fields like radiology and pathology. However, the application of CNNs in dermatology, which is also based on images, is very limited. Inflammatory skin diseases, such as psoriasis (Pso), eczema (Ecz), and atopic dermatitis (AD), are very easily to be mis-diagnosed in practice. Methods: Based on the EfficientNet-b4 CNN algorithm, we developed an artificial intellig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 18 publications
1
27
1
Order By: Relevance
“…Wu et al showed that multi-lesion skin disease can be classified at the level of single-lesion skin disease, on highly selected image material (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al showed that multi-lesion skin disease can be classified at the level of single-lesion skin disease, on highly selected image material (13).…”
Section: Discussionmentioning
confidence: 99%
“…This model achieved a 67-75% sensitivity in diagnosing multiple-lesion skin disease (including acne, eczema, and psoriasis). Recently Wu et al did show an impressive 95% overall diagnostic accuracy in classifying atopic dermatitis, eczema and psoriasis on selected image material (13). Studies comparing the accuracy of CAD models to clinicians are generally based on image classification equivalent to retrospective analysis, though some head to head studies were conducted with prospective collected image material (12,14,15).…”
Section: Introductionmentioning
confidence: 99%
“…Our model was based on the recently proposed EfficientNet that achieved better accuracy and efficiency (6.1 times faster) with a smaller number of model parameters (8.4 times less) than other networks [23]. It has been applied to solve medical problems, such as the diagnosis of COVID-19 [24,25] and the classification of skin diseases [26]. EfficientNet utilizes a new scaling method, so-called compound coefficient, to systematically balance the depth (d: the length of the model), width (w: the number of channels) and resolution (r: the image size) of a given network.…”
Section: Effeicient-b0 Networkmentioning
confidence: 99%
“…In a recent study, a high confusion rate of Pso with Ecz was reported given the similar appearance of these skin lesions. Therefore, the diagnostic e ciency of single-model DLS of clinical skin images may be limited by the imitating nature of LE skin lesions 21 . Given the lack of characteristic and well-directed pathological changes in LE lesions, the application of single-model DLS of HE staining images in LE may not be as effective as its application in cancer tissue 22 .…”
Section: Introductionmentioning
confidence: 99%